Knowledge of Cervical Cancer and Uptake of Human Papillomavirus Vaccine among Mothers of Adolescents in Ibadan, Nigeria. (2023)
Cervical cancer (CC) is the most common gynecological malignancy in Nigeria, and the Human papillomavirus (HPV) is known to be associated with the disease. Vaccination is an effective preventive strategy, but its uptake remains low in Nigeria. Therefore, this study aimed to assess the knowledge and uptake of HPV vaccination among mothers of adolescents in two selected markets in Ibadan, Nigeria. A descriptive cross- sectional design was employed, and 398 mothers were purposively selected out of the 600 accessible participants. Data was collected using a structured interviewer-administered questionnaire and analyzed using IBM Statistical Package for the Social Sciences version 25. Descriptive statistics, frequency tables, and charts were used for data presentation, while the chi- square test was used for hypothesis testing at a significance level of 0.05. The findings revealed that 46.7% of the respondents were aged 39-48 years. Less than half (47.2%) had a high knowledge level of Cervical cancer and HPV, and only 23.4% had received HPV vaccination, with none of their daughters being vaccinated against HPV. The major perceived factors influencing mothers' uptake of HPV vaccine were a lack of adequate information about the vaccine (87.2%) and not knowing where to get the vaccine (79.4%). There was no significant association between mothers' knowledge and uptake of the HPV vaccine (p=0.487), as well as the cost of the vaccine and its uptake (p=0.998). However, a significant association was found between mothers' educational level and their knowledge of cervical cancer (p=0.000). These findings highlight the need for improved information dissemination on cervical cancer and HPV vaccination. It is recommended that the government initiates national immunization policies to make the vaccine more accessible and affordable, thereby combating the disease effectively.